DINASTI MAMALIK DI MESIR - Nur, Abdullah (Hunafa: Jurnal Studia Islamika, 2005)
In Islamic history, the succession of a dinasty to another is natural. The Mamluk dinasty is one of dinaties that reaches its peak of power from the thirteenth to the sixteenth century. The suceess of this dinasty is much supported by its perfecting military and governmental sistem. This style of this governmance ,in turn, leads to a powerful military and a well-managed administration. In addition, it gains progress in economic diplomacy, commercial agreement with France, Italy and other European countries. A rapid advancement of science also takes place in the regime and even bears outstanding scientists in each of their expertise. As a result, art and culture develope rapidly.Kata kunci: Dinasti Mamalik, Mesir